The Impact of Surgery-induced Inflammation on Anti-neoplastic Immunity and Metastasis - Hallgren, Beatrice (My University, 2019)
The trauma associated with cancer surgery may trigger the release of tumor cells into the blood stream along with a systemic inflammatory response that hampers immunosurveillance. Both these factors might enhance the risk of development of distant metastases. Myeloid cells express the NOX2-enzyme that generates reactive oxygen species (ROS) that participate in the clearance of pathogens. However, extracellularly released NOX2-derived ROS may also triggers dysfunction and apoptosis in adjacent anti-neoplastic lymphocytes. Myeloid cells produce enhanced levels of NOX2-derived reactive oxygen species (ROS) during infection, but also during inflammation and cancer. In this study, we explored the role for NOX2-derived ROS in surgery-induced immunosuppression and metastasis formation in vivo by the use of a wounding model. To mimic surgery-related inflammation, sterile polyvinyl alcohol (PVA) sponges were implanted s.c. to WT and NOX2-deficient (Nox2-/-) mice one week before injection of B16F10 melanoma cells into the blood stream. The presence of implanted sponges increased the number of lung metastases in WT mice but not in corresponding Nox2-/- mice. Moreover, treatment with the NOX2 inhibitor histamine dihydrochloride (HDC) significantly reduced the formation of metastases in inflamed WT mice. Blood was drawn from WT and Nox2-/- mice one week after the sponge implantation to determine the extent of the inflammatory response. In sponge-bearing WT mice, there was a significant increase in the frequency of Ly6C+ inflammatory monocytes (p<0.001, n=22) and in their formation of ROS (p<0.01, n=14). No increase in inflammatory monocytes was noted in sponge-bearing Nox2-/- mice (p>0.5, n=8). In vivo treatment with HDC completely prevented the increase in inflammatory monocytes in wounded WT mice (p<0.001, n=10). Additionally, we investigated the impact of inflammation on metastasis formed spontaneously from a solid tumor where we observed higher incidence of tumor outgrowth in sponge-bearing mice. These data suggest that surgical inflammation augments inflammatory monocyte levels in blood and their NOX2-derived ROS production, which may impair immunosurveillance and enhance metastasis.
Keywords: Immunologi; Cell- och molekylärbiologi; Immunologi inom det medicinska området; Livsvetenskaper; Immunology; Cell and Molecular Biology; Immunology in the medical area; Life Science